2014
DOI: 10.1080/03075079.2014.980399
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the up, back, and forward-component in master's thesis supervision with adaptivity

Abstract: Despite the importance of goals in educational theories, goals in master's thesis projects are rarely investigated. Therefore, this study explores how goals play a role in master's thesis supervision in terms of: defining the goals (up-component); locating where the student stands in relation to the goals (back-component); and how the student can more closely reach the goals (forward-component). Twelve supervisors and students were interviewed and the adaptive approach of supervision emerged as a recurrent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 39 publications
(51 reference statements)
0
16
0
1
Order By: Relevance
“…For supervisors, it is important to realize that conducting EDR as an early career researcher brings about a range of insecurities and challenges that can differ depending on researcher personalities, previous experiences with research, and participation in other communities. Given the important role supervisors play in facilitating the successful completion of a PhD trajectory (González-Ocampo et al, 2015), we suggest that supervisors need to adapt their supervision to the specific challenges that PhD students experience, referred to as "adaptivity" in the context of in the context of Master's thesis supervision (de Kleijn, Bronkhorst, Meijer, Pilot, & Brekelmans, 2014). Yet, PhD students and supervisors should not avoid insecurities altogether, as they can carry learning potential.…”
Section: Discussionmentioning
confidence: 99%
“…For supervisors, it is important to realize that conducting EDR as an early career researcher brings about a range of insecurities and challenges that can differ depending on researcher personalities, previous experiences with research, and participation in other communities. Given the important role supervisors play in facilitating the successful completion of a PhD trajectory (González-Ocampo et al, 2015), we suggest that supervisors need to adapt their supervision to the specific challenges that PhD students experience, referred to as "adaptivity" in the context of in the context of Master's thesis supervision (de Kleijn, Bronkhorst, Meijer, Pilot, & Brekelmans, 2014). Yet, PhD students and supervisors should not avoid insecurities altogether, as they can carry learning potential.…”
Section: Discussionmentioning
confidence: 99%
“…De Kleijn, Bronkhorst, Meijer, Pilot, and Brekelmans (2014) examined 12 mentorstudent dyads and found that thesis mentors provided support that was adapted to their own goals and to students' goals. These mentors collected information about the students and sometimes the mentors explicitly formulated a student's characteristic that they observed.…”
Section: Teachers' Diagnosticsmentioning
confidence: 99%
“…This paper builds on results from primary/secondary education and applies this research literature to the HE context. Given the fact that the quality of the diagnosing process is crucial for adaptive mentoring and student learning (de Kleijn et al, 2014(de Kleijn et al, , 2015Hedin & Gaffney, 2013), and the knowledge that, in general, teachers' diagnostic processes need to be improved (Südkamp et al, 2012), it is worthwhile to unravel the diagnostic process involved in thesis mentoring.…”
Section: Teachers' Diagnosticsmentioning
confidence: 99%
“…Even when supported by a supervisor, the dissertation is commonly associated with a greater degree of independent learning than previous assessments (Todd, Bannister and Clegg 2004;Anderson, Day and McLaughlin 2006;Greenbank and Penketh 2009). It is allocated more time and credit and students have a greater role to play in determining the topic and focus of their work (de Kleijn et al 2016). Independent learning is central to university study in the UK, requiring students to take responsibility for and make decisions regarding their own learning (HEA 2014).…”
Section: The Dissertation and Independent Learningmentioning
confidence: 99%